The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsomega.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanowire/Carbon Sheet Composites for Electrochemical Syngas Generation with Tunable H2/CO Ratios

Abstract: Generating syngas (H 2 and CO mixture) from electrochemically reduced CO 2 in an aqueous solution is one of the sustainable strategies utilizing atmospheric CO 2 in value-added products. However, a conventional single-component metal catalyst, such as Ag, Au, or Zn, exhibits potential-dependent CO 2 reduction selectivity, which could result in temporal variation of syngas composition and limit its use in large-scale ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Recently, a number of catalysts, including cadmium sulfoselenide nanorods, 16 Cu-enriched Au, 15 silver nanowire/ carbon sheet composites, 19 and silver diphosphide nanocrystals, 20 have been demonstrated as active catalysts for ECR syngas formation. However, ECR technologies are still far from being economically completive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of catalysts, including cadmium sulfoselenide nanorods, 16 Cu-enriched Au, 15 silver nanowire/ carbon sheet composites, 19 and silver diphosphide nanocrystals, 20 have been demonstrated as active catalysts for ECR syngas formation. However, ECR technologies are still far from being economically completive.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly employed 0.5 M KHCO 3 aqueous electrolyte solution saturated with CO 2 (pH = 7.5) was used as catholyte. 21,24,26,29 The fluidic characteristics of the employed cell design allowed to recirculate the catholyte solution (flow rate of 20 ml/min), while the CO 2 gas was directly injected through the macroporous 3D Cu-Ag…”
Section: Electrochemical Reduction Of Comentioning
confidence: 99%
“…In this regard, dendritic structures are of particular interest and were targeted in this study. Besides numerous examples of Ag based materials for CO 2 RR to CO, such as nanoplates, 20 nanoporous material and nanoparticles, [21][22][23][24][25] nanowires, 26,27 nanoclusters 28 and porous foams, 29 , dendritic structures offer large active surface areas paired with facile and non-expensive synthetization. [30][31][32] In this regard, we selected the electrodeposition method to deposit the Ag catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…25 A number of researchers have demonstrated that Ag promotes CO evolution in both aqueous and non-aqueous systems with varying electrokinetics that are largely influenced by the surface morphology and nature of electrolyte adsorption at the electrode-electrolyte interface. 25,26,27 It has also been shown that oxide derived nanostructured Ag materials exhibit excellent ability to convert CO2 to CO with selectivities exceeding 80%.…”
Section: Introductionmentioning
confidence: 99%